El control interno y el proceso logístico en la Gerencia Sub Regional de Ucayali - Contamana año 2022 - Gonzales Souza, Esther del Pilar (2022)
The general objective of the research was to determine the relationship between internal control and the logistics process in the Sub Regional Management of Ucayali – Contamana year 2022., in which an applied type study, correlational level and non-experimental design was chosen, where It took 120 workers as a population, to whom the survey technique was applied and the question questionnaire as an instrument. Among the results, it was possible to determine that the internal control is qualified as regular, because they always provide them with the updated ROF, and disciplinary actions are almost always applied, but sometimes guidelines and policies are disseminated, as well as provides ICT technical support, however, staff almost always have access to information, and sometimes self-assessment is performed. On the other hand, the logistics process is qualified as regular, since the Logistics Area staff is duly trained, while sometimes they comply with the execution of the annual contracting plan, and all stored goods are codified, as well as Sometimes the acquisition procedure is fulfilled. In conclusion, it was determined that there is a significant relationship between internal control and logistics process, which has been contracted by a correlation coefficient of 0.531, being a positive average level, and a (bilateral) significance of 0.000.